2018
DOI: 10.1111/jsbm.12411
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs’ Resources, Technology Strategy, and New Technology‐Based Firms’ Performance

Abstract: This study is based on the configuration approach and argues that the new technology‐based venture's performance depends on how well the entrepreneur's resources allow the chosen technology strategy to be executed, in other words, the fit between the resources and the strategy. The authors study this idea by using a sample of 175 Spanish new technology‐based ventures. The results indicate that the fit between the chosen technology strategy and the entrepreneur's resources explain the firm's performance, when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…Successful implementation of this plan depends on the adequate identification and management of human and social resources (such as knowledge, access to technology, work experience in large companies, etc.) [Garcia-Cabrera et al, 2019]. However, technological resources alone are not enough to ensure competitiveness.…”
Section: Technological Level Of Productsmentioning
confidence: 99%
“…Successful implementation of this plan depends on the adequate identification and management of human and social resources (such as knowledge, access to technology, work experience in large companies, etc.) [Garcia-Cabrera et al, 2019]. However, technological resources alone are not enough to ensure competitiveness.…”
Section: Technological Level Of Productsmentioning
confidence: 99%
“…We use a dummy indicator as a proxy of superior financial outcomes. First, we followed García-Cabrera et al (2019) and considered the NTBF's profits (earnings before taxes) as financial indicator of outcome. We obtained information from the SABI database, so this financial information was quantitative and not provided by the surveyed entrepreneurs.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that NTBFs require more than one founder to handle the complexity of technology ventures, but founding teams should not be too large to guarantee positive team dynamics (Wang and Chen 2016), which are necessary in order to share knowledge resources. In addition, managerial knowledge is necessary to successfully introduce new products into the market or to make proper decisions about internationalisation (García-Cabrera et al 2019). Second, specific human capital refers to technology education, as well as industry experience (Nuscheler et al 2019).…”
Section: Human Capital External Sources Of Knowledge and Venture Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The successful implementation of this plan depends upon the adequate identification and management of human and social resources (such as knowledge, access to technology, work experience in large companies, etc.) [Garcia-Cabrera et al, 2019]. However, technological resources alone are not enough to ensure competitiveness.…”
Section: Technological Level Of Productsmentioning
confidence: 99%